Energy Transition in the global South – Editorial for the International Journal of Sustainable Energy Planning and Management Vol 35 - Østergaard, Poul Alberg; Johannsen, Rasmus Magni (International Journal of Sustainable Energy Planning and Management, 2022)
This 35th volume of the International Journal of Sustainable Energy Planning and Management includes work investigating different biomass resource utilisation scenarios for Mexico as well as scenarios for the transition of Thailand. The latter finds significant photo voltaic requirements when factoring in the transition to green hydrogen for transportation. Transportation is also the focal point in a study of Indonesia, finding that cost and emission optimisation are pushing optimum in different directions. Continuing with Indonesia, the country is seeing a rapidly growing electricity demand, and Siregar investigates social, environmental, technical, and economic criteria for the development of the system towards a more sustainable electricity supply. The scenario analyses are largely based on larger societal transitions, but Appiah makes a more concerted effort to investigate the actual investments in renewable energy sources. Lastly, an article focuses on the industrial sector and how energy efficiency may be affected by policies.